The mitochondria as a potential therapeutic target in cerebral I/R injury - Fang, Susu; Huang, Wenzhou; Qu, Xinhui; Chai, Wen (Frontiers in Neuroscience, 2025)
Ischemic stroke is a major cause of mortality and disability worldwide. Among patients with ischemic stroke, the primary treatment goal is to reduce acute cerebral ischemic injury and limit the infarct size in a timely manner by ensuring effective cerebral reperfusion through the administration of either intravenous thrombolysis or endovascular therapy. However, reperfusion can induce neuronal death, known as cerebral reperfusion injury, for which effective therapies are lacking. Accumulating data supports a paradigm whereby cerebral ischemia/reperfusion (I/R) injury is coupled with impaired mitochondrial function, contributing to the pathogenesis of ischemic stroke. Herein, we review recent evidence demonstrating a heterogeneous mitochondrial response following cerebral I/R injury, placing a specific focus on mitochondrial protein modifications, reactive oxygen species, calcium (Ca2+), inflammation, and quality control under experimental conditions using animal models.